Fragmento tectónico cabo frio: aspectos de campo, petrografía e geoquímica - Fonseca, Ariadne do Carmo (Anuário do Instituto de Geociências, 1994)
The main lithological units which occur in the "Cabo Frio Tectonic Fragment" are orthogneisses and paragneisses. The orthogneisses have granitic-granodioritic-tonalitic compositions, with amphibolitic enclaves and intercalations and are cutted by granitic aplites. The paragneisses are metapelites, with intercalations of amphibolite, quartzites and calc-silicate rocks, metamorphosed in upper amphibolite facies, in intermediate pressure conditions. Geochemically, the orthogneisses correspond to a metaluminous high-K calc-alkalic series, with monzogabbro, quartz-monzodiorite and monzonite compositions. Otherwise, the petrography indicates a low-K calc-alkalic series, suggesting a pre-collisional granitoids series related to oceanic crust subduction. A divergence between the compositions obtained by the petrography and geochemistry can be the result of problems in the analyses of alkalies. The amphibolites, associated to the orthogneisses, also present calc-alkalic metaluminous character, with basaltic and andesitic compositions, suggestive of orogenic emplacement. The paragneisses show compositions varying between lithoarenite and arkoses, with peraluminous character, probably deposited in a continental are or ative continental margin environment.